ANALYZING ALEXANDER WENDT’S STATEMENTS REGARDING "ANARCHY IS WHAT THE STATE MAKES IT" - Zauzah, Nino Zeh (SIYAR Journal, 2024)
Many nations in the global arena are undergoing state system reforms to enhance their countries' conditions. Many nations employ anarchic systems, although the question remains if these state systems will outperform other countries in terms of efficiency. This concept is strongly connected to Alexander Wendt’s statement regarding the nature of anarchy being determined by the state. This statement is strongly connected to Alexander Wendt’s assertion that anarchy is determined by the actions and policies of the state. This study aims to analyse the conceptual framework of these terms and explore the significance of Alexander Wendt’s remarks, particularly their connection to an improved state structure. This study employs a qualitative methodology, utilising several reviews of literature for collecting data. The analysis of this study suggests that Alexander Wendt employs a constructivist framework that will subsequently change the global system for the better. This is because the state is unable to function independently without external intervention, thus requiring transformative changes.